THE SOCIAL DISCRIMINATION BETWEEN LABOR CLASS AND CAPITAL CLASS THAT REFLECTED IN THE WILLIAM BLAKE’S POEM - -, Nopriansah; Ekonanto, Firli (JURNAL LITERARY CRITICISM, 2014)
The purpose of the this study is to perform how does the impacts of social discrimination between labor class and capital class during industrial revolution in England (1750-1850) and how does the condition of labor class that reflected in the william Blake?s poem. This research used Mimetic theory that is how to analized the literary work as a reflection the reality life based on the author?s imagination and Sociology of literature that is how far the author?s social life influence the story in a literary work. Through the poems entitled; London, Chimney sweeper, Infant sorrow, The little boy lost, Ah sun flower, The sick rose, The land of dream and Infant joy, william Blake whishes to described about the suffering of labor class especially for children and women who are exploitated by capital class, they are compiled to work in the factory to cost their life but in fact during work in the factory they had the unfair treatments or inhumane from the capital class, they are given the low wages by the long of work time so that this condition creates suffering for them, but on the other hand the capital class lived in luxury, and then in his poems he also to make allusion to the kingdom and church side who are unable giving solution to solve the condition, pricesly they have conspired to the capital class for getting benefit. Finally through his poems he is able to rise the spirit of freedom human nature which he desire to existence the equal of rights, social status, and wiping out the all of discrimination form. Keywords: William Blake, poem, Industrial Revolution, impact social     discrimination, labor class and capital class.